Exploring determinants influencing the selection of geriatric nursing care services in Thailand Bangkok metropolitan area - Triyuth Promsiri; Budsara Arunyik; Vasu Keerativutisest (Edelweiss Applied Science and Technology, 2024)
The global population structure is undergoing a significant transformation, marked by an increasing number of elderly individuals. Thailand, in particular, is transitioning into an aging society and exhibits the third-highest growth rate in Asia, following Japan and Singapore. This phenomenon is driven by various factors, including economic and social conditions, technological advancements, family dynamics, and evolving lifestyles. Consequently, a growing number of elderly individuals are either living alone or require caregivers and elderly care facilities if they are dependent. This study is prompted by a keen interest in the elderly care service industry, which demonstrates significant potential both currently and in the future. The primary objective of this research is to explore the determinants influencing the selection of Geriatric nursing care and to identify the challenges encountered in delivering these services. The study investigated demographic and social factors, the necessity for elderly care, and the decision-making process in selecting geriatric nursing care. Data was collected through online questionnaires and analyzed, employing both descriptive and inferential statistics, including factor analysis, reliability analysis, and correlations between variables. The target population comprises Thai individuals aged 50 and above residing in Bangkok and its metropolitan areas with a sample size of 426 participants. Findings suggest that demographic factors, excluding occupation, along with social factors, the necessity for dependency, and the decision-making process, affect the selection of Geriatric nursing care in the studied regions.
Keywords: Intergenerational Family Dynamics and Caregiving; Healthcare Systems and Reforms; Global Healthcare and Medical Tourism